1999
DOI: 10.1677/joe.0.1610503
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-induced downregulation of receptors for TGF-beta in human osteoblast-like cells from adult donors

Abstract: High concentrations of transforming growth factor b (TGF-) are found in the bone matrix, reflecting a pivotal role of this growth factor in the coupling of bone resorption and formation. TGF-strongly stimulates the synthesis of extracellular matrix proteins, but in vitro studies show an inhibitory effect on the final mineralization process, which in vivo occurs despite high concentrations of TGF-. Little is known about how bone-forming cells respond to different concentrations of TGF-and if they can transientl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 30 publications
3
16
0
2
Order By: Relevance
“…As described previously in detail, human osteoblasts exhibit the property of markedly downregulating the number of cell surface receptors for TGF-ß after incubation with the ligand [24]. In order to investigate whether or not osteoblasts from donors with OI differ with respect to this adaptive response, cells from OI patients were preincubated for 18 h with 40 pM TGF-ß1 prior to bind-Gebken/Brenner/Feydt/Notbohm/ Brinckmann/Müller/Bätge ing studies with 125 I-TGF-ß1.…”
Section: Ligand-induced Downregulation Of Receptors For Tgf-ßmentioning
confidence: 75%
“…As described previously in detail, human osteoblasts exhibit the property of markedly downregulating the number of cell surface receptors for TGF-ß after incubation with the ligand [24]. In order to investigate whether or not osteoblasts from donors with OI differ with respect to this adaptive response, cells from OI patients were preincubated for 18 h with 40 pM TGF-ß1 prior to bind-Gebken/Brenner/Feydt/Notbohm/ Brinckmann/Müller/Bätge ing studies with 125 I-TGF-ß1.…”
Section: Ligand-induced Downregulation Of Receptors For Tgf-ßmentioning
confidence: 75%
“…3D). It is believed that overdoses of growth factors can suppress expression of their own receptors 34,35 possibly through enhanced receptor degradation. 36 Futureinquiries into changes in receptor numbers due to their interactions with other environmental factors such as ECM 37 are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation is that elongated cells at the periphery of TGF-b1 constructs expressed a minimal level of TGF-bRII (Fig. 3D), the molecule associated with the initial binding of TGF-b and triggering subsequent intracellular reactions, 35 so they were blocked from receiving TGF-b1 signals, and thus acted like normal chondrocytes. Supportively, a recent study showed that high doses of TGF-b (10 ng/mL) can suppress collagen I synthesis by fibroblasts via upregulation of CUX1.…”
Section: Discussionmentioning
confidence: 99%
“…For example, TGF-β1 mRNA levels are increased in human AD brains (20), which may be due to local tissue injury or reflect an attempt to compensate for the reduction in TβRII expression. Alternatively, excess ligand can reduce TβRII levels (37). Interestingly, levels of the neurotrophin receptors TRKA and TRKB are also decreased in AD, specifically in neurons affected by the disease (4, 38, 39).…”
Section: Discussionmentioning
confidence: 99%